2022
DOI: 10.1038/s41419-022-04821-w
|View full text |Cite
|
Sign up to set email alerts
|

Impacts and mechanisms of metabolic reprogramming of tumor microenvironment for immunotherapy in gastric cancer

Abstract: Metabolic disorders and abnormal immune function changes occur in tumor tissues and cells to varying degrees. There is increasing evidence that reprogrammed energy metabolism contributes to the development of tumor suppressive immune microenvironment and influences the course of gastric cancer (GC). Current studies have found that tumor microenvironment (TME) also has important clinicopathological significance in predicting prognosis and therapeutic efficacy. Novel approaches targeting TME therapy, such as imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 187 publications
(204 reference statements)
0
43
0
Order By: Relevance
“…Optimization of existing compounds and continued search and development of new LDHA inhibitors will be reasonable strategies to obtain direct antitumor effects or enhance, for example, immunotherapy results ( 48 , 124 , 125 ). For example, since the effect of immunotherapy can be prevented by lactate ( 79 , 80 ) and high LDH levels before treatment are correlated with a poor response to immunotherapy ( 126 , 127 ), inhibition of LDHA can improve the efficacy of anti-PD-1 therapy ( 128 ).…”
Section: Tumor Acidity As a Target Of Treatmentmentioning
confidence: 99%
“…Optimization of existing compounds and continued search and development of new LDHA inhibitors will be reasonable strategies to obtain direct antitumor effects or enhance, for example, immunotherapy results ( 48 , 124 , 125 ). For example, since the effect of immunotherapy can be prevented by lactate ( 79 , 80 ) and high LDH levels before treatment are correlated with a poor response to immunotherapy ( 126 , 127 ), inhibition of LDHA can improve the efficacy of anti-PD-1 therapy ( 128 ).…”
Section: Tumor Acidity As a Target Of Treatmentmentioning
confidence: 99%
“…Increasing evidence has shown that the tumor microenvironment (TME) is widely involved in tumor development and progression, chemoradiotherapy and immune therapy (31)(32)(33). TME is mainly composed of tumor cells and stromal components, of which stromal components consist of residential fibroblasts, endothelial cells, infiltrating immune cells, secreted cytokines and chemokines, and nascent blood and lymphatic vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, metabolic reprogramming, arising from H. pylori infection has been shown to drive immunosuppression [ 74 ]. Infection with H. pylori upregulates Lon protease 1 expression and increases glycolysis [ 75 ].…”
Section: Role Of Chronic Infection With Helicobacter Pylori...mentioning
confidence: 99%